PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DALAM PEMBELAJARAN IPA SISWA KELAS IV SDN 34 AIR PACAH PADANG - Citra Adelia; Gusmawetti Gusmawetti; Yulfia Nora (Program Studi PGSD FKIP Universitas Bung Hatta, 2020)
This research aims to describe the difference in learning outcomes of cognitive and affective aspects of IPA students by applying cooperative learning model type Two Stay Two Stray with conventional method in class IV SD 34 Air Pacah Padang. The type of research is experimental research. Place of study at SD 34 Air Pacah Padang with the number of research sample there are two classes that is student class IV A and IV B with amount of student 49 student. Analyze technique using t -test. The results showed that the learning outcomes of cognitive aspects of the average IPA in the experimental class is 86.25 and the control class is 74.8. Hypothesis testing using t-test shows tcount> ttable, with tcount of 2,91 and ttable value equal to 1,68 at significant level significant 0,05. The learning outcomes of the affective aspects of experimental class and control class with experimental grade grade were 75.83 and 70.63. Hypothesis testing using t-test shows tcount> ttable, with tcount value of 1.81 and ttable value equal to 1.68 at significant level significant 0,05. Based on the result of this research, it can be concluded that there is a significa nt difference between the cognitive aspect and affective of the experimental and control class students using the Two Stay Two Stray learning model